The contribution of ion channels to shaping macrophage behaviour - Selezneva, Anna; Gibb, Alasdair J.; Willis, Dean (Frontiers in Pharmacology, 2022)
The expanding roles of macrophages in physiological and pathophysiological mechanisms now include normal tissue homeostasis, tissue repair and regeneration, including neuronal tissue, initiation, progression, and resolution of the inflammatory response and a diverse array of anti-microbial activities. Two hallmarks of macrophage activity which appear to be fundamental to their diverse cellular functionalities are cellular plasticity and phenotypic heterogeneity. Macrophage plasticity allows these cells to take on a broad spectrum of differing cellular phenotypes in response to local and possibly previous environmental signals. Cellular plasticity also contributes to tissue- and stimulus-dependent macrophage heterogeneity, which manifests itself as different macrophage phenotypes being found at different tissue locations and after different cell stimuli. Together, plasticity and heterogeneity align macrophage phenotypes to their required local cellular functions and prevent inappropriate activation of the cell, which could lead to pathology. To execute the appropriate function, which must be regulated at the qualitative, quantitative, spatial and temporal levels, macrophages constantly monitor intracellular and extracellular parameters to initiate and control the appropriate cell signaling cascades. It is, therefore, not surprising that the sensors and signaling mechanisms which control macrophages are the focus of a considerable amount of research. Ion channels regulate the flow of ions between cellular membranes and are critical to cell signaling mechanisms in a variety of cellular functions. It is surprising that the role of ion channels in the macrophage biology has been relatively overlooked. In this review we provide a summary of ion channel research in macrophages. We begin by giving a narrative-based explanation of the membrane potential and its importance in cell biology. We then report on research implicating different ion channel families in macrophage functions. Finally, we highlight some areas of ion channel research in macrophages which need to be addressed and future possible developments in this field.